2019
DOI: 10.1155/2019/5496346
|View full text |Cite
|
Sign up to set email alerts
|

Additional Effects of Nutritional Antioxidant Supplementation on Peripheral Muscle during Pulmonary Rehabilitation in COPD Patients: A Randomized Controlled Trial

Abstract: Background. Skeletal muscle dysfunction in patients with chronic obstructive pulmonary disease (COPD) is not fully reversed by exercise training. Antioxidants are critical for muscle homeostasis and adaptation to training. However, COPD patients experience antioxidant deficits that worsen after training and might impact their muscle response to training. Nutritional antioxidant supplementation in combination with pulmonary rehabilitation (PR) would further improve muscle function, oxidative stress, and PR outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 41 publications
1
35
0
Order By: Relevance
“…An updated study in 2019 showed that oral antioxidant supplementation, which comprised tocopherol, ascorbate, zinc gluconate, and selenomethionine during moderate-intensity exercise training for 28 days, increased muscle strength, serum protein, and plasma antioxidant compounds in COPD patients, when compared to non-antioxidant supplementation during exercise training. 37 Moreover, elderly people showed low antioxidant status, especially in L-ascorbic acid (Vit C), including lower muscle mass, strength and increased walking speed. 38,39 Previous evidence showed that supplement of Vit C combined with alpha-tocopherol for 4 weeks decreased the creatine kinase (CK) level in marathon runners, 40 and furthermore, stimulated the immune function by activating white blood cell proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…An updated study in 2019 showed that oral antioxidant supplementation, which comprised tocopherol, ascorbate, zinc gluconate, and selenomethionine during moderate-intensity exercise training for 28 days, increased muscle strength, serum protein, and plasma antioxidant compounds in COPD patients, when compared to non-antioxidant supplementation during exercise training. 37 Moreover, elderly people showed low antioxidant status, especially in L-ascorbic acid (Vit C), including lower muscle mass, strength and increased walking speed. 38,39 Previous evidence showed that supplement of Vit C combined with alpha-tocopherol for 4 weeks decreased the creatine kinase (CK) level in marathon runners, 40 and furthermore, stimulated the immune function by activating white blood cell proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…76 Furthermore, a nutritional supplement characterized by the presence of both, with specific contributions equal to 180 mg/day of vitamin C and 30 mg day α-tocopherol, associated with zinc (15 mg/day) and selenium (50 μg/ day) in patients with COPD undergoing pulmonary rehabilitation treatment showed significant improvements in muscle strength, suggesting a potential "add-on" effect. 77 Other anti-oxidants, such as beta-cryptoxanthin, lutein zeaxanthin, retinol, beta-carotene and lycopene, both blood and food, were positively associated with FEV1%, supporting the hypothesis that an imbalance in the state antioxidant/oxidant is associated with chronic airflow limitation. 78 In conclusion, it is favorably useful to modify the lifestyle by adding (a) large quantities of fruit, vegetables (5 portions per day: 3 of fruit and 2 of vegetables, 1 raw and cooked), 52 (b) whole foods, to increase the fiber share, 79 and (c) antioxidants in order to improve FEV1 and oxidative stress.…”
Section: Fiber and Antioxidantsmentioning
confidence: 76%
“…Only in malnourished patients has nutritional supplementation demonstrated significant improvements for 6-minute walk test, respiratory muscle strength and health status. 286 A 12-month nutritional intervention in muscle wasted patients had no effect on physical capacity but physical activity was significantly higher. 287…”
Section: Therapy Relevant To All Patients With Copdmentioning
confidence: 94%